Efeito da fototerapia com LED azul e vermelho sobre o metabolismo de células pulpares em cultura - Almeida, Leopoldina de Fátima Dantas de [UNESP] (2015)
The  overall  aim  of  this  work  was  to  evaluate  the  effects  of  the  low  level   phototherapy  using  light  emitting  diodes  (LEDs)  at  the  blue  (455nm)  and  red   (630nm)  wavelengths  on  the  metabolism  of  pulp  cells  in  culture.  Four  studies  were   performed.  In  the  first  study,  the  effect  of  red  LEDs  on  MDPC-‐23  cells  was   investigated,  using  a  fixed  energy  dose  of  2J/cm2  and  varying  the  density  of  potency   in  20  and  40mW/cm2  and  the  frequency  of  irradiation.  Cell  viability,  number  of  viable   cells  and  production  of  total  protein  were  analyzed  after  24h  from  the  irradiation.  In   the  second  study  it  was  evaluated  the  effect  of  the  blue  light  on  MDPC-‐23  cells.  The   energy  doses  of  2  or  4J/cm2  with  a  dose  of  potency  of  20mW/cm2  were  delivered  to   the  cells.  Cell  viability,  number  of  viable  cells,  cell  morphology  in  SEM  and  gene   expression  for  alkaline  phosphatase  (Alp),  collagen  (Col-‐I)  and  dentin  matrix  protein   (Dmp-‐1)  were  analyzed.  The  third  study  investigated  the  transdentinal  effects  of  a   blue  and  red  light  on  MDPC-‐23  cells.  The  densities  of  potencies  were  adjusted  in  40   and  80mW/cm2  for  the  blue  and  red  lights,  respectively.  After  irradiation  of  the  cell   culture,  cell  viability,  alkaline  phosphatase  activity,  production  of  total  protein  and   collagen  were  determined.  Lastly,  the  biostimulatory  effect  of  the  blue  light  on  a   primary  culture  of  human  pulp  was  investigated  in  the  fourth  study. .. (Complete abstract electronic access below)